2020
DOI: 10.3390/antiox9111095
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs as Sensors of Oxidative Stress in Neurodegenerative Diseases

Abstract: Oxidative stress (OS) results from an imbalance between the production of reactive oxygen species and the cellular antioxidant capacity. OS plays a central role in neurodegenerative diseases, where the progressive accumulation of reactive oxygen species induces mitochondrial dysfunction, protein aggregation and inflammation. Regulatory non-protein-coding RNAs (ncRNAs) are essential transcriptional and post-transcriptional gene expression controllers, showing a highly regulated expression in space (cell types),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 270 publications
0
14
0
Order By: Relevance
“…Noncoding RNAs are implicated in a wide variety of cellular processes, as well as in many disease conditions [ 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ] in which the oxidative stress alters ROS homeostasis. Oxidative stress induces the expression of several transcription factors such as NFκB, AP-1, p53, HIF-1α, PPAR-γ, β-catenin/Wnt, and Nrf2 that, in turn, activate the expression of hundreds of genes which are associated with growth factors signaling, immune responses, and cell cycle transition.…”
Section: Possible Therapeutic Target To Protect the Nvumentioning
confidence: 99%
“…Noncoding RNAs are implicated in a wide variety of cellular processes, as well as in many disease conditions [ 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ] in which the oxidative stress alters ROS homeostasis. Oxidative stress induces the expression of several transcription factors such as NFκB, AP-1, p53, HIF-1α, PPAR-γ, β-catenin/Wnt, and Nrf2 that, in turn, activate the expression of hundreds of genes which are associated with growth factors signaling, immune responses, and cell cycle transition.…”
Section: Possible Therapeutic Target To Protect the Nvumentioning
confidence: 99%
“…Neuronal death, whether apoptosis or necrosis, is caused by a variety of mechanisms related to DNAm. Studies on genetic and environmental factors in neurodegenerative diseases have shown that the imbalance between oxidative and antioxidant systems, caused by the increase in reactive oxygen species (ROS) and the deficiency of antioxidant capacity, is the main contributor to oxidative stress [ 113 ], which ultimately leads to neuronal death [ 113 , 114 ]. Treadmill exercise can reverse the related neuronal loss by preventing oxidative damage of DNA [ 115 ].…”
Section: Dnam For Neuroplasticity Neuronal Loss and Neurogenesis Under Exercisementioning
confidence: 99%
“…MicroRNAs or miRNAs are short (20-24 nucleotides) regulatory ncRNAs that were first discovered in C. elegans in 1993 (Lee et al 1993). They are one of the major negative posttranscriptional modulators and act by imperfect complementary base pairing with mRNA, resulting in recruitment of various RNA degrading factors or protein translation inhibition (Gámez-Valero et al 2020). They modulate the cellular response to FR toxicity inducing inflammation, mitochondrial impairment, aberrant protein and lipid modifications, nucleic acid damage, and gene expression changes (Tönnies and Trushina 2017).…”
Section: Interference Of Micrornas To Inhibit Free Radical Activitymentioning
confidence: 99%